The Effect of Lavender Aromatherapy for Quality Sleeping in Postpartum Mothers - Dencik, Devina Anggrainy (Yayasan Ahmad Mansyur Nasirah, 2025)
The postpartum period is an important period for mothers after giving birth, where many physiological and psychological changes occur that can affect the quality of life, one of which is sleep quality. Lack of quality sleep can have a negative impact on physical recovery, mental health, and the relationship between mother and baby. This study aims to determine the effect of lavender aromatherapy on the quality of sleep of postpartum mothers at PMB Lismarini Palembang. This study employed a quasi-experimental pretest-posttest one-group design. Aromatherapy is given by direct inhalation by dripping 5 drops of lavender essential oil onto a handkerchief and then inhaling it directly for 10 minutes for 7 days. The study population consisted of 30 postpartum mothers in the PMB Lismarini Palembang area who experienced sleep disorders, selected using a total sampling technique. Data analysis was performed using univariate and bivariate methods. Sleep quality assessment using the Pittsburgh Sleep Quality Index (PSQI) with criteria ≤ 5 for good and > 5 for bad. The research results show that the average sleep quality of postpartum mothers before giving lavender aromatherapy was 6.2 or included in the poor sleep quality category, and the average sleep quality after giving lavender aromatherapy was 4.7 or included in the good sleep quality category. It was concluded that a significant effect was found (p = 0.004), indicating that lavender aromatherapy improved postpartum mothers' sleep quality. Research with larger samples and more complex research designs, such as clinical trials with stricter control groups, is needed.